2013
DOI: 10.3390/md11125159
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Neuroprotective Action of Xyloketal Derivatives in Parkinson’s Disease Models

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease affecting people over age 55. Oxidative stress actively participates in the dopaminergic (DA) neuron degeneration of PD. Xyloketals are a series of natural compounds from marine mangrove fungus strain No. 2508 that have been reported to protect against neurotoxicity through their antioxidant properties. However, their protection versus 1-methyl-4-phenylpyridinium (MPP+)-induced neurotoxicity is only modest, and appropriate structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…We first reported the protective effects of Xyl-B on an oxLDL (oxidatively modified low density lipoprotein)-induced endothelial injury [9] . Furthermore, Xyl-B was shown to have multiple biomedical activities, including neuroprotective effects against toxicity, antioxidant effects on endothelial cells and zebrafish, anti-glioma effects through the inhibition of TRPM7 and the reduction of atherosclerosis plaque formation in apolipoprotein E-deficiency mice [10][11][12][13][14][15][16] . Our previous study also demonstrated that Xyl-B protected against neonatal brain injuries induced by hypoxiaischemia [17] .…”
Section: Hemodynamics Of the Regional Cerebral Perfusionmentioning
confidence: 99%
“…We first reported the protective effects of Xyl-B on an oxLDL (oxidatively modified low density lipoprotein)-induced endothelial injury [9] . Furthermore, Xyl-B was shown to have multiple biomedical activities, including neuroprotective effects against toxicity, antioxidant effects on endothelial cells and zebrafish, anti-glioma effects through the inhibition of TRPM7 and the reduction of atherosclerosis plaque formation in apolipoprotein E-deficiency mice [10][11][12][13][14][15][16] . Our previous study also demonstrated that Xyl-B protected against neonatal brain injuries induced by hypoxiaischemia [17] .…”
Section: Hemodynamics Of the Regional Cerebral Perfusionmentioning
confidence: 99%
“…Molecular modeling of interaction between active compounds and αsynuclein suggests that more potent and selective derivatives might be possible as well as provide insight into the mechanism of anti-aggregation. Xyloketal derivatives have also been developed as potential neuroprotective agents in PD [38]. In C. elegans animals with dopaminergic neuron degeneration produced by 1-methyl-4-phenylpyridinium (MPP+), the survival rate could be significantly increased with several derivatives.…”
Section: Pharmacological Stuediesmentioning
confidence: 99%
“…Recently, Liu and colleagues demonstrated that novel xyloketal derivatives protected against H 2 O 2 -induced injury in an in-vitro model of oxidative damage [11]. In addition, the same group has previously synthesized xyloketal derivatives that significantly attenuated reactive oxygen species (ROS) production in zebrafish, increased the survival rates of Caenorhabditis elegans and protected against neurodegeneration in C57BL/6 mice in an in-vivo model of PD [12]. These neuroprotective effects are likely mediated by the antioxidative properties of xyloketals.…”
Section: Antioxidative Properties Of Xyloketalsmentioning
confidence: 99%